Performance science domains: Contemporary strategies for teams preparing for the Rugby World Cup - Kilduff, L. P.; Pyne, D. B.; Cook, C. J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: As the start of the 10th Rugby Union World Cup approaches, performance staff will be working on the final elements of their teams` preparation. Much of this planning and preparation will be underpinned by the latest performance science research. In this invited commentary, we discuss contemporary performance science research in rugby union centered around 4 key performance domains. First, we outline a systematic approach to developing an overall understanding of the game demands and how performance staff can enhance the players` preparedness for competition. We then move on to outline our understanding of the training science domain, followed by a brief overview of effective recovery strategies at major tournaments. Finally, we outline research in the area of competition-day strategies and how they can positively impact players` readiness to compete.